2012
DOI: 10.1063/1.4748258
|View full text |Cite
|
Sign up to set email alerts
|

Cold collisions of polyatomic molecular radicals with S-state atoms in a magnetic field: An ab initio study of He + ${\rm CH}_2(\tilde{X})$ CH 2(X̃) collisions

Abstract: We develop a rigorous quantum mechanical theory for collisions of polyatomic molecular radicals with S-state atoms in the presence of an external magnetic field. The theory is based on a fully uncoupled space-fixed basis set representation of the multichannel scattering wave function. Explicit expressions are presented for the matrix elements of the scattering Hamiltonian for spin-1/2 and spin-1 polyatomic molecular radicals interacting with structureless targets. The theory is applied to calculate the cross s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 80 publications
(186 reference statements)
0
13
0
Order By: Relevance
“…Later Stuhl et al [21] pointedo ut that to reduce the number of required laser frequencies J 0 ¼ J 00 À 1t ype transitions could be used to eliminate rotational branching. Following these initial proposals, laser cooling and slowing has been demonstrated on the diatomic radicals SrF, [22,23] YO, [50,117] and CaF, [24,25] and led to the creationo f am agneto-optical trap (MOT) for SrF. [29,31] Polyatomic molecules possess extra atoms compared to diatomics,l eadingt oa dditional degrees of freedom and complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Later Stuhl et al [21] pointedo ut that to reduce the number of required laser frequencies J 0 ¼ J 00 À 1t ype transitions could be used to eliminate rotational branching. Following these initial proposals, laser cooling and slowing has been demonstrated on the diatomic radicals SrF, [22,23] YO, [50,117] and CaF, [24,25] and led to the creationo f am agneto-optical trap (MOT) for SrF. [29,31] Polyatomic molecules possess extra atoms compared to diatomics,l eadingt oa dditional degrees of freedom and complexity.…”
Section: Introductionmentioning
confidence: 99%
“…180 In this case the dissociation occurs through coupling between Zeeman levels of the bound and unbound channels and the magnitude of the coupling is varied by changing the external magnetic field. The possibility of sympathetic cooling of magnetically trapped polyatomic molecules by 1 S 0 -state atoms, including alkaline earth atoms, was explored by Tscherbul et al 181,182 Coupled-channel quantum calculations of He + CH 2 indicate that the collision induced spin-relaxation rate is too slow to cause trap loss. 181 Spin relaxation also occurs slowly in collisions of spinpolarized CaH with Li atoms in a magnetic field despite the significant anisotropy of the Li-CaH interaction, 183 making Li atoms a promising cooling medium for CaH molecules.…”
Section: Inelastic Scattering In the Presence Of External Fieldsmentioning
confidence: 99%
“…We showed that despite the strong angular anisotropy of the interactions between 2 Σ molecular radicals and alkali-metal atoms, the inelastic cross sections for interspecies collisions are strongly suppressed due to the weakness of the spin-rotation interaction in 2 Σ molecules [29]. Small polyatomic molecular radicals such as methylene (CH 2 ), methyl (CH 3 ), and amidogen (NH 2 ) were found to have small spin relaxation cross sections with S-state atoms, and hence suggested as promising candidates for sympathetic cooling experiments in a magnetic trap [30,31]. Magnetic trapping of CH 3 radicals has been accomplished in a recent experiment [32].…”
Section: Introductionmentioning
confidence: 99%
“…Cooling and trapping polyatomic molecular radicals is expected to provide new insights into many-mode vibrational dynamics, photochemistry, and chemical reactivity at ultralow temperatures [20,[30][31][32][35][36][37] [20,36].…”
Section: Introductionmentioning
confidence: 99%